(untitled) (AKULTURASI, 2022)
Abstract The purpose of the study was to examine whether the public knew about the functions and benefits of the services at PPN Kwandang and to determine the public’s perception of the services and facilities of PPN Kwandang. This study used a survey method and continued with interviews as well as distributing questionnaires. The population in this study were fishermen, port employees and the general public. The number of samples taken was 50 respondents using the sampling method of fishermen 20 respondents, 20 employees and the general public 10. The results of this study used Gutman scale and Likert scale analysis. The data collected in the form of primary data and secondary data. Primary data were collected directly by researchers through interviews and questionnaires. Secondary data obtained from the agency. The results of the study using a Guttman scale analysis of fishermen’s perceptions of the service knowledge of the functions and benefits of port facilities 77% already know the functions and benefits of the services provided by PPN Kwandang, while 23% say they do not know the functions and benefits of services provided by PPN Kwandang. Perceptions of port employees 98% already know the service functions and benefits of the Kwandang PPN facility and do not know 0.4%. The general public 90% already know and 10% do not know. The average respondent stated that it was very good, meaning that the respondent was very aware of the service functions and benefits of the facility. The results of the Likert scale analysis regarding port facilities have the highest average dimension for fishermen’s perceptions, which is 4.37%, which means that fishermen’s perceptions are very good. The employee’s perception of the highest dimension of 4.36% is still very good, and the general public’s perception of the highest dimension of 4.64 is also very good. For fishermen’s perceptions of service, the highest dimension is 4.35%, employee perception is 4.37% and the general public is 4.36, the criteria for this question are very good and positive regarding respondents’ perceptions. Â Keywords: perception; society; PPN Kwandang Â Abstrak Tujuan penelitian adalah untuk mengkaji apakah masyarakat mengetahui tentang fungsi dan manfaat layanan yang ada di PPN Kwandang serta untuk mengetahui persepsi masyarakat terhadap layanan dan fasilitas PPN Kwandang. Penelitian ini menggunakan metode survey dan dilanjutkan dengan wawancara sekaligus pembagian kuesioner. Populasi dalam penelitian ini adalah nelayan, pegawai pelabuhan dan masyarakat umum. Jumlah sampel yang diambil sebanyak 50 responden dengan menggunakan metode sampling responden nelayan 20, pegawai 20 dan masyarakat umum 10 orang. Hasil penelitian ini menggunakan analisis skala gutman dan skala likert. Data yang dikumpulkan berupa data primer dan data sekunder. Data primer dikumpulkan langsung peneliti melalui wawancara dan kuesioner. Data sekunder diperoleh dari instansi. Hasil penelitian menggunakan analisis skala Guttman persepsi nelayan mengenai layanan pengetahuan fungsi dan manfaat fasilitas pelabuhan 77% sudah mengetahui fungsi dan manfaat layanan yang disediakan oleh PPN Kwandang, sedangkan 23% menyatakan tidak mengetahui fungsi dan manfaat layanan yang disediakan oleh PPN Kwandang. Persepsi pegawai pelabuhan 98% sudah mengetahui layanan fungsi dan manfaat fasilitas PPN Kwandang dan tidak mengetahui 0,4%. Masyarakat umum 90% sudah mengetahui dan 10% tidak mengetahui. Rata-rata responden menyatakan sangat baik artinya responden sangat mengetahui layanan fungsi dan manfaat fasilitas. Hasil analisis skala likert mengenai fasilitas pelabuhan rataan dimensi yang paling tinggi untuk persepsi nelayan yaitu 4,37% yang berarti persepsi nelayan sangat baik. Persepsi pegawai rataan dimensi yang paling tinggi 4,36% masih sangat baik, dan persepsi masyarakat umum rataan dimensi yang paling tinggi 4,64 tergolong sangat baik juga. Untuk persepsi nelayan mengenai layanan yang paling tinggi dimensinya 4,35% persepsi pegawai paling tinggi 4,37% dan masyarakat umum 4,36, kriteria pertanyaan ini yang sangat baik dan positif mengenai persepsi responden. Â Kata kunci: persepsi; masyarakat; PPN Kwandang